The Effect of Phosphorus and Potassium on the Growth and Quality of Viola (Viola cornuta L.) Seed Production - Alfa Sada Saputra; Suprihati Suprihati; Endang Pudjihartati (Caraka Tani: Journal of Sustainable Agriculture, 2020)
Viola cornuta L. is an ornamental plant that is primarily propagated by high-quality seeds that have high demand in subtropical countries. The use of fertilizers according to recommendations results in the growth of parent plants below the standard. Furthermore, seed production is generated below 2 g per plant and the seed germination capacity is below 80%. In addition, phosphorus (P) and potassium (K) nutrients can increase the growth and seed production of the plants, including ornamental plants. The study aimed to determine the influence of P and K nutrients on growth and seed production of V. cornuta L. Research was carried out in November 2018 - January 2019 at PT. Selektani Horticulture, Ngablak, Magelang. There were seven treatments with four replications. Experiments were arranged according to the Randomized Complete Block Design (RCBD). Plants were grown in 5l volume-polybags. Fertilization was done by watering the planting media. Analysis of variance was performed at 95% accuracy. The study shows that P and K nutrients have a highly significant effect on height, number of flowers, number of seed per capsule, seed production and germination energy and significantly affected the number of leaves. The addition of both P and K fertilizers in the vegetative and P in the generative stage (P6) can result in the productivity of 3.28 g plant-1 and produce germination energy ≥90%. It is recommended for increasing growth and seed production.